How Excessive Use of Smartphone Are Becoming Loneliness In Young Adult - Maisarah Maisarah; Maya Khairani (Seurune : Jurnal Psikologi Unsyiah, 2023)
Arguing that maintaining a separate relationship at a distance is closer, the consequences of excessive use of smartphones can actually reduce physical closeness by making people who are physically close to further. Loneliness is the subjective psychological discomfort people experience when their network of social relationships is significantly deficient in either quality or quantity. The objective of the present study was to investigate the relationship between smartphone addiction and loneliness among young adults. The population in this study were young adults of Aceh. These samples included 400 young adults in Aceh. The sampling technique used was unrestricted self-selected surveys. Data collection tools used are Smartphone Addiction Scale and University of California Los Angeles (UCLA) Loneliness Scale Version 3. The reliability of the scale of smartphone addiction and loneliness in this study .912 and .888. The analysis used in the parametric method was product-moment correlation analysis. The result showed there was a positive and significant correlation between smartphone addiction and loneliness (r = .432, p.05).